EFFICIENCY ANALYSIS OF POLYCRYSTALLINE AND AMORPHOUS SOLAR CELLS IN CLOUDY SKY CONDITIONS OF QUETTA - Bakhsh, Sunila; Khan, Shoibullah; Khalid, Muhammad (European Scientific Journal, ESJ, 2015)
Amongst the renewable energy resource solar energy has achieved a high remark. The solar energy being a sustainable energy source is used now-a-days for power generation. There are several ways to employing the solar energy directly. For example the use of PV technology for direct conversion of sunlight into electricity and the other method is the use of solar thermal systems e.g. solar collectors. Researchers around the world showed that the efficiency of the solar cells is greatly affected by the climate of a particular region, such as Omubo-Pepple et al. (2009) showed that there exists a strong relationship between solar irradiance and cell temperature on the efficiency of solar cells. Mieke (1998) compared the efficiency of two different types of solar cells for a hot climate of Jilkminggan (Australia). In this research paper the efficiencies of the p-si and a-si technology are compared in a cloudy sky condition.